BEYOND CENTRE: A PSYCHO-FEMINISTIC READING OF HILARY MANTEL’S GIVING UP THE GHOST (International Journal of Food and Nutritional Sciences, 2022)
The literary genre ‘Autobiography’ emerged as a result of the writers considering their psychological ‘self’ expression as authoritative and having much influence on the world or being influenced by it. Men writers, for centuries, through associating themselves with the government or political groups and in turn bought a ‘self’ centered writing based on their experience and observations.